Influence of machining parameters on microdrill performance. (25th February 2011) - Hemanth, G.; Samuel, G.L.; Vasa, N.J.
There is an increasing interest in microdrilling of metallic and other miniaturised components. Drill breakage is the most prevalent problem with microdrill that possesses high length-to-diameter ratio. In this paper, finite element modelling approach is used to determine the buckling load of a microdrill while drilling metallic components. The influence of variation in flute length, diameter, helix angle and lip angle on buckling load during machining of metallic components is studied. Empirical loading equation based on the material hardness, feed and diameter of the microdrill is also used to estimate the loading condition during microdrilling operation. Results are in agreement with the buckling loads predicted by proposed finite element model. In the present work emphasis is made on estimating the critical feed and the speed based on modal analysis while machining various materials. Tool failure can be avoided by maintaining the machining conditions within these critical operating parameters.